Toward a Holistic Integration of Digital Technologies in Physical Education: Global Perspectives, Pedagogical Frameworks, and Critical Considerations - Malhotra, Deepika; Mehta, Vineet (Indian Journal of Educational Technology, 2025)
Rapid developments in digital technology are transforming how we teach and learn, including in Physical Education (PE). This paper examines the use of digital tools—such as video feedback, mobile apps, social media, virtual reality (VR), and artificial intelligence (AI)—in PE. It offers an overview of key theories, international viewpoints, and practical examples. Drawing on models such as Social Cognitive Theory and TPACK, it explores how technology can enhance motor skill acquisition, enrich assessment practices, and foster self-regulated learning. Case studies highlight the potential for innovative tools to improve motivation, engagement, and skill development, while also identifying key challenges related to resource disparities, teacher training, privacy concerns, and the potential overemphasis on performance metrics. The analysis emphasises that realising the full potential of technology in PE requires a careful balance between innovation and pedagogical intentionality. Strategies for effective professional development, curriculum design, and supportive policies are discussed. This paper articulates a vision for a holistic, ethically grounded, and learner-centred approach to integrating digital tools in PE by situating current practices within historical contexts and emerging trends. It concludes by offering research directions and policy recommendations to ensure that technology serves as a means to enrich, rather than replace, meaningful physical education experiences.